(untitled) (Academia Journal of Medicine, 2026)
Regenerative endodontic procedures have emerged as a paradigm-shifting approach in the management of immature permanent teeth with pulp necrosis, offering a biologically driven alternative to traditional apexification techniques. Unlike conventional approaches that merely create an apical barrier, regenerative strategies aim to restore functional pulp like tissue within the root canal system, thereby promoting continued root development, dentinal wall thickening, and apical closure. The biological foundation of regenerative endodontics rests upon three fundamental pillars of tissue engineering: stem cells, bioactive scaffolds, and growth factors. Stem cells of the apical papilla, surviving within the periapical region even after pulp necrosis, represent a critical cellular resource capable of differentiating into odontoblast-like cells and contributing to the formation of mineralized tissue. Clinical protocols have evolved considerably since the earliest case reports, with contemporary guidelines emphasizing thorough canal disinfection using minimally cytotoxic irrigants and intracanal medicaments, followed by the intentional induction of a blood clot scaffold through periapical instrumentation. Bioactive materials such as mineral trioxide aggregate and bioceramic cements serve as coronal barriers, providing a biocompatible seal that supports tissue regeneration. Reported clinical outcomes include resolution of periapical pathology, continued root lengthening, increased root wall thickness, and apical closure, although the histological nature of the regenerated tissue remains a subject of ongoing investigation. This narrative review comprehensively examines the biological underpinnings, contemporary clinical protocols, and documented outcomes of regenerative endodontic procedures, while critically evaluating current controversies, limitations, and future directions in this rapidly evolving field.